"So What's the Difference?" Talking About Race With Refugee Children in the English Language Learner Classroom. Issue 3 (11th August 2016) - Roy, Laura
Abstract : This study examines how an English language learner (ELL) educator negotiated conversations about the intersectional nature of race in an elementary ELL classroom using a critical literacy framework. Few studies examine the ways in which teachers of young children negotiate conversations about the complexities of race with their students. Even fewer address the way in which African refugee children can explore the contested nature of racial labeling as a part of language instruction in the classroom. The students in this study experienced a history of persecution and displacement in Somalia in the 1990s. Their experiences in Somalia, relocation to refugee camps in Kenya, and finally relocation to the United States exposed their families to the very real impact of static and stereotypical notions of race. Through the lens of critical literacy, classroom interactions and activities are analyzed through one cycle of literacy events in an ELL classroom. Findings show that ELL educators can explore the contested nature of racial identities in ways that support and enhance language instruction. Findings also highlight the complexities of immigrant and refugee identity positions, even among members of the same group.